HUBUNGAN MINAT BELAJAR MATEMATIKA DENGAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS 5 MI MATHLA’UL ANWAR 1 SINDANG BARANG KOTA BOGOR - Nabillah Rahmawati; Chodidjah Makarim; Gunawan Ikhtiono (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2021)
Interest in learning is someone's own desire, which gives rise to new knowledge and experiences. With the interest in learning will affect student learning outcomes, this is the student's interest in something in the learning activity itself. This study aims to determine the interest in learning mathematics, determine the factors that affect the interest in learning mathematics, determine the learning outcomes of mathematics, and determine the relationship between the interest in learning mathematics and mathematics learning outcomes in grade 5 students of MI Mathlaul Anwar 1 Sindang Barang, Bogor City. Data obtained from questionnaires using the existing population of 60 respondents. The type of research used is ex-postfacto with the method used in this study is the correlation method with a quantitative approach. Based on the research results, the interest in learning mathematics in grade 5 students at MI Mathlaul Anwar 1 Sindang Barang, Bogor City can be said to be sufficient, this can be seen through the average points on the variable interest in mathematics learning questionnaire which is equal to 78.33. While the results of learning mathematics in grade 5 at MI Mathla'ul Anwar 1 Bogor City are in the moderate category. This can be seen through the average value of the mid-semester assessment (PTS), which is 78.12. This is based on the above analysis, the correlation value for variable X and variable Y is 0.28 which is located between the interval 0.20 -0.40 which means that there is a weak relationship. then by looking at the table on